2014
DOI: 10.1177/0269216314560208
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ and nurses’ views and experience of transferring patients from critical care home to die: A qualitative exploratory study

Abstract: Background:Dying patients would prefer to die at home, and therefore a goal of end-of-life care is to offer choice regarding where patients die. However, whether it is feasible to offer this option to patients within critical care units and whether teams are willing to consider this option has gained limited exploration internationally.Aim:To examine current experiences of, practices in and views towards transferring patients in critical care settings home to die.Design:Exploratory two-stage qualitative studyS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 20 publications
0
46
1
Order By: Relevance
“…Participants reported being unable to manage facilitating patients to experience a good death, that is a death that "encompass[es] no suffering (both from physical and psychosocial distress), dying at a preferred place, being around family, not being a burden to others and a 'sense of completion of their familial responsibilities during the last days of life" (Vencatasalu, Clarke & Atkinson, 2015, p. 1677. Although previous research has demonstrated the interplay of patient and system related factors on transferring patients from critical care home to die (Coombs, Long-Sutehall, Darlington & Richardson, 2015), our analysis shows that wider structural factors frequently contribute to difficulties in organising such complex discharges (Ingleton, Payne, Sargeant & Seymour, 2009). …”
Section: Discussioncontrasting
confidence: 65%
“…Participants reported being unable to manage facilitating patients to experience a good death, that is a death that "encompass[es] no suffering (both from physical and psychosocial distress), dying at a preferred place, being around family, not being a burden to others and a 'sense of completion of their familial responsibilities during the last days of life" (Vencatasalu, Clarke & Atkinson, 2015, p. 1677. Although previous research has demonstrated the interplay of patient and system related factors on transferring patients from critical care home to die (Coombs, Long-Sutehall, Darlington & Richardson, 2015), our analysis shows that wider structural factors frequently contribute to difficulties in organising such complex discharges (Ingleton, Payne, Sargeant & Seymour, 2009). …”
Section: Discussioncontrasting
confidence: 65%
“…It is encouraging that, despite an increase in severity of disease, the odds of intensive care unit (ICU) mortality have reduced (Vincent et al 2018). For those patients who are unlikely to survive, there is also increasing evidence of more open discussions about priorities of care, as reflected in scientific and conceptual papers (Coombs et al 2015, Van del Bulcke et al, 2018. Despite this progress towards more explicit communication about death and dying with patients and families in ICU, studies conducted by Jang & colleagues (2019) and Betriana & colleagues (2019) illustrate that this open-ness stops short of acknowledging the impact of a patient's death on health care professionals.…”
Section: Final Approved Versionmentioning
confidence: 99%
“…Cases reporting on the discharge of critically, but also terminally, ill patients are more limited and are still rare events in the United Kingdom . This is despite the fact that mortality in critical care is relatively high, and it is an accepted opinion that people would prefer to die at home .…”
Section: Introductionmentioning
confidence: 99%